La "chipana" que aún arrastra la evaluación para llegar a una calidad educativa en el Perú - Morán Martinez, Valeria (2010)
For many decades now, education has been an essential right. The Political Constitution, within its legal framework, set forth in one of its articles the promotion of education as upheld by the Universal Declaration of Human rights and the Convention on the Rights of the Child. This is the starting point for highlighting how important it is to receive not only an education, but  an education of quality.